Interactions between climate change mitigation and adaptation: The case of hydropower in Brazil. (1st December 2018) - Lucena, André F.P.; Hejazi, Mohamad; Vasquez-Arroyo, Eveline; Turner, Sean; Köberle, Alexandre C.; Daenzer, Kathryn; Rochedo, Pedro R.R.; Kober, Tom; Cai, Yongxia; Beach, Robert H.; Gernaat, David; van Vuuren, Detlef P.; et al.
Abstract: This paper performs a multi-model comparison to assess strategies for adaptation to climate change impacts in hydropower generation in Brazil under two Representative Concentration Pathways. The approach used allows for evaluating the interactions between climate change mitigation and adaptation strategies under low and high impact scenarios through 2050. Climate change impact projections of sixteen General Circulation Models indicate that a global high emissions trajectory scenario would likely yield more severe impacts on hydropower generation than a mitigation scenario. Adaptation modeling suggests that climate change impacts can be compensated by a wide range of alternatives, whose optimality will depend on the level of mitigation effort pursued. Our results show that climate change impacts would lead to even higher emissions in the absence of climate change mitigation policies. On the other hand, mitigation strategies to pursue lower emissions are maintained under climate change impacts, meaning that mitigation strategies are robust when faced with adaptation challenges. Mitigation efforts could yield a more diverse and less carbon intensive mix of technological options for adaptation. When analyzing investment costs to adapt to climate change impacts, in some cases mitigation can lead to a lower total investment level. Highlights: Climate change impacts on hydropower are assessed for sixteen models and two scenarios. Interactions between climate change mitigation and adaptation are analyzed. Adaptation/mitigation strategies from six different energy models are compared. Adaptation and mitigation investment costs are assessed and compared.